289 OOKINETE SECRETION OF A HIGH-MOLECULAR-WEIGHT COMPLEX-MEDIATING SERINE PROTEASE ACTIVATION OF A MALARIA PARASITE PROCHITINASE CRITICAL FOR MALARIA TRANSMISSION. Issue 1 (1st January 2007) - Dehority, W.; Li, F.; Vinetz, J.
Abstract : Background: The mosquito invasive form of the malaria parasite, the ookinete, secretes chitinases critical for mosquito invasion and continuation of the parasite life cycle. This class of enzyme is validated as a target for interrupting malaria transmission. A recombinant zymogen form of the P. gallinaceum chitinase rPgCHT1 was previously shown to be activated in vitro by the serine protease Endoproteinase Lys-C. Objective: To test the hypothesis that an ookinete-produced serine protease activates pro-PgCHT1, we sought to characterize this enzyme toward the goal of validating this protease as a target of blocking malaria transmission. Methods: Conditioned ookinete culture medium was subjected to a benzamidine (serine protease inhibitor) affinity column. The ability of the eluate to activate pro-rPgCHT1 in the presence and absence of the serine protease inhibitor AEBSF and the aspartic acid protease inhibitor pepstatin A was assessed using a microfluorimetry assay, which measured chitinase activity expressed as relative fluorescence units (RFU)/minute. Results: Eluate containing 11.1 μg of protein increased the activity of 11.1 μg of rPgCHT1 from 30 RFU/minute to 488 RFU/minute ( p = .002). This effect was diminished by 21% following the addition of the serine protease inhibitor AEBSF ( p = .046) but not by the aspartic protease inhibitor pepstatin A. Eluate without rPgCHT1 had 477 RFU/minute of chitinase activity, significantly higher than rPgCHT1 by itself ( p = .003) but not significantly different from eluate and rPgCHT1 together ( p = .64). The addition of AEBSF to eluate decreased activity by 23% ( p = .017), with no effect seen following the addition of pepstatin A. Discussion: Benzamidine-column eluate of P. gallinaceum ookinete culture supernatants proteolytically activated pro-rPgCHT1. This eluate also possessed intrinsic chitinase activity, suggesting the cosecretion of PgCHT1 and serine protease activity in a complex. These findings are novel for apicomplexan parasites and have practical application toward developing novel approaches to blocking malaria transmission.